Peningkatan domain kognitif, afektif dan psikomotor dalam program pembelajaran di luar kampus pada mahasiswa fakultas ilmu kesehatan universitas muhammadiyah lamongan: Improvement of cognitive, affective and psychomotor domains in off-campus learning programs for students of the faculty of health sciences, universitas muhammadiyah lamongan - Faridah, Virgianti Nur; Aris, Arifal; Sholikhah, Siti; Nurafifah, Dian; Prastiwi, Riana (Bali Medika Jurnal, 2021)
Background : Universities in the health sector have basically implemented independent learning, especially off-campus learning long before the “Kampus Merdeka” policy was launched, but it is still limited to one program of activities, namely internships/work practices. This is a challenge for the health study program to be able to design and implement an innovative off-campus learning process in eight activities while still paying attention to learning outcomes covering the domains of attitudes, knowledge, and skills optimally. This study aims to see learning outcomes covering cognitive, affective and psychomotor domains during off-campus learning activities carried out by study programs at the Faculty of Health Sciences, University Muhammadiyah Lamongan. Method : This study uses a survey method by distributing questionnaires to all FIKES UMLA students. as many as 960 students (total sampling) consisting of 683 undergraduate students in Nursing, 95 undergraduate students in Hospital Administration and 182 undergraduate students in Pharmacy. This survey research uses quantitative data analysis techniques with a descriptive approach. Results : The results obtained from the cognitive domain of 96.15% stated that there was an increase when learning was carried out outside the campus, the affective domain was 96.15% and the psychomotor domain was 95.83%. Conclusion : Off-campus learning programs are able to improve learning outcomes covering cognitive, affective and psychomotor domains.